2017
DOI: 10.1161/jaha.117.006708
|View full text |Cite
|
Sign up to set email alerts
|

Vena Cava Filter Retrieval Rates and Factors Associated With Retrieval in a Large US Cohort

Abstract: BackgroundRetrieval of vena cava filters (VCFs) is important for safety as complications increase with longer dwell times. This study assessed VCF retrieval rates and factors associated with retrieval in a national cohort.Methods and Results VCFs were identified by procedural codes from an administrative claims database. Patients were identified who had a VCF placement during a hospitalization from a national commercial administrative claims database. Indications for VCF placement were identified as pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 42 publications
0
39
1
Order By: Relevance
“…In addition, a recently published study reviewed state-wide filter placement and retrieval rates in New York and reported an overall retrieval rate of 3.5% between 2005 and 2014 21 . Our retrieval rates are notably lower than those reported by Brown et al, who utilized a national private insurance claims database and estimated an overall retrieval rate of 18.4% 22 . The lower age, lower proportion of Medicare patients, and ability to account for mortality as a competing risk all likely contributed to a higher estimate of retrieval rates by these investigators compared to our study; however, despite all these factors, the authors still found a lower retrieval rate than would be expected based on single-center data.…”
Section: Discussioncontrasting
confidence: 89%
“…In addition, a recently published study reviewed state-wide filter placement and retrieval rates in New York and reported an overall retrieval rate of 3.5% between 2005 and 2014 21 . Our retrieval rates are notably lower than those reported by Brown et al, who utilized a national private insurance claims database and estimated an overall retrieval rate of 18.4% 22 . The lower age, lower proportion of Medicare patients, and ability to account for mortality as a competing risk all likely contributed to a higher estimate of retrieval rates by these investigators compared to our study; however, despite all these factors, the authors still found a lower retrieval rate than would be expected based on single-center data.…”
Section: Discussioncontrasting
confidence: 89%
“…It is widely reported that the rate of removal of retrievable IVC filters is suboptimal (41). There are also limited safety data on the long-term outcomes of filters designed with retrieval or conversion capabilities.…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…An additional marker of quality of care for IVCF patients would include retrieval for non-permanent devices between hospitals as retrieval rates have been reported to be only 10-40%. 18,[31][32][33] However, retrieval is often done on an outpatient basis and would not be observable in inpatient discharge data.…”
Section: Limitationsmentioning
confidence: 99%